It Is Not Just Mortality: A Call from Chile for Comprehensive Covid-19 Policy Responses Among Older People - Villalobos-Dintrans, P (Gerontological Society of America, 2021)
Objective: Provide a synthesis of the COVID-19 policies targeting older people in Chile, stressing their short- A nd long-term challenges. Method: Critical analysis of the current legal and policy measures, based on national-level data and international experiences. Results: Although several policies have been enacted to protect older people from COVID-19, these measures could have important unintended negative consequences in this group s mental and physical health, as well as financial aspects. Discussion: A wider perspective is needed to include a broader definition of health-considering financial scarcity, access to health services, mental health issues, and long-term care-in the policy responses to COVID-19 targeted to older people in Chile. © 2020 The Author(s). Published by Oxford University Press on behalf of The Gerontological Society of America. All rights reserved.